Islamic Worldview for Ethical Dimension of Islamic Communication - Taqiyuddin, Muhammad; Yudhistira, Bagus; Fadillah, Rizki Maulana (Proceeding International Conference on Science and Engineering, 2021)
Abstract. Islam as a universal religion is a religion that does not only contain values and spiritual aspects and a set of rituals of worship. But more than that as proof of its universality, Islam is capable and proven to be able to penetrate various lines and boundaries of geographic and cultural cultures, as well as various scientific fields and the science of communication is no exception. Ethics as the basis of religion in social life has a close relationship with the tradition of communication science, because communication science is a practical science that cannot be separated from people’s life. The dynamic condition of modern society has influenced this science. Digital media which is an important part of modern society as a means of communication has made communication science follow its development. And this is the reason why ethics in social life with ethics in social media in the midst of modern society cannot be separated, which is the main object of discussion in this paper.